The The Effect of Discovery Learning Model Assisted by CERMAT Educational Game on Mathematical Problem-Solving Ability of Trigonometric - Reza Fahlevi; Eka Firmansyah; Nani Supriati (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2024)
This study aims to determine the effect of Discovery Learning Model learning assisted by the CERMAT educational game on mathematical problem-solving skills on the concept of Trigonometry. This type of research is quasi-experimental research using Pretest-Posttest Control Group Design, which is data collection using tests (essays) supported by N-gain data analysis with variance tests to determine the difference in character in each group (experimental and control). The CERMAT educational game media is the main learning media containing student worksheets, and quizzes (formative test questions). This type of educational game is categorised as RPG (Role Playing Game). The subjects of this study consisted of a sample of 59 class X students at SMKN 12 Bandung. The data collection technique used was a pretest-posttest problem-solving skills test in the form of 5 questions about trigonometry material; 2.) student response questionnaire with as many as 20 statements. In the experimental group, the learning used was the discovery learning model assisted by the CERMAT educational game, while the control group only used the discovery learning model without the CERMAT educational game. The results of data analysis show that the average N-Gain test results of 67.9511 or 67,95% are included in the moderately effective category, and the results of the Mann-Whitney Difference Test show that the Discovery Learning Model assisted by the CERMAT Educational Game Media has a significant effect on improving the mathematical problem-solving skills of students in Class X SMKN 12 Bandung which has an impact on improving learning outcomes, especially on the concept of Trigonometry.